Evolution of public transit modes in a commuter corridor. (February 2017) - Sun, Yanshuo; Guo, Qianwen; Schonfeld, Paul; Li, Zhongfei
Highlights: The selection of public transit modes is optimized over a planning horizon. A minimum economic length for a rail line exists and can be determined numerically. Economies of scale favor large extensions and excess supplied capacity. The rail-only service is largely dominated by the feeder-trunk service, even in the long run. Abstract: This paper explores how the selection of public transit modes can be optimized over a planning horizon. This conceptual analysis sacrifices geographic detail in order to better highlight the relations among important factors. First, a set of static models is proposed to identify which type of service, e.g., bus only, rail only, or bus and rail, is the most cost-effective in terms of the average trip cost for given demand. After analyzing essential factors in a long-term planning process, e.g., economies of scale in rail extension and future cost discounting, a dynamic model incorporating such considerations is formulated to optimize the decision over a planning horizon. While analytical solutions can be obtained for some decision variables, the final model is solved with a graphical method by exploring the tradeoffs between the initial and recurring costs. Major findings from this study include: (a) there exists a minimum economic length for a rail line, which can be determined numerically; (b) economies of scale favor large extensions and excess supplied capacity; (c) the rail-only service is largely dominated by the feeder-trunk service, even in the long run.